First-in-human cases and preclinical experience of a novel ICE catheter - Liu, Guangan; Wu, Jingjing; Fang, Fang; Zhao, Weipeng; Sun, Minmin; Zhang, Jihong; Liu, Simeng; Wang, Mimi; Liu, Feng (Frontiers in Cardiovascular Medicine, 2024)
To verify the safety and effectiveness of the novel intracardiac echocardiography (ICE) catheter, we conducted a First-in-Human study and preclinical in vitro tests, comparing it with established commercial ICE catheters. This report describes the utilization of the new ICE catheter in aiding arrhythmias electrophysiology ablation, with a comparative analysis of its performance against existing competitors in porcine models. Background Since the 1960s, the use of intracardiac echocardiography (ICE) catheters has been showcased globally. Notably, in 1981, Glassman and Kronzon made a significant contribution by embedding a 7.5MHz ultrasonic into a flexible coaxial cable, which was then utilized in 20 patients 1 . Although the prototype emerged early, technological advances in ICE have not kept pace with those of its peers. Furthermore, it's noteworthy that ultrasound imaging is the only major medical imaging modality for which no one has been awarded a Nobel Prize, since the development depending on many prior insights from physics 2 . In 2000, the first phased-array AcuNAV 10 French (10F) catheter (Johnson and Johnson MedTech) was introduced to global market, and since then, it has maintained a dominant position for more than 20 years. With the onset of the new century, rapid developments in fields such as structural heart and electrophysiology diseases have propelled ICE into new applications 3,4,5,6 . The demand of visualizing small cardiac structures, including valves, left atrial appendage and left atrial wall, has driven the adoption of 3D and 4D ICE 6,7,8,9 . In comparison to the well-stablished transesophageal echocardiography (TEE), ICE presents unique advantages, offering high spatial resolution for imaging at short distances and eliminating the need for general anesthesia 8,10,11 . Despite its cost disadvantage, ICE has demonstrated its value in various intervention procedures. Meanwhile, besides the AcuNAV and ViewFlex ICE (Abbott Laboratories) catheters,